Where Did the Women Go?: Female Artists from the Ottoman Empire to the Early Years of the Turkish Republic - Shaw, Wendy M. K (Journal of women's history, 2011)
This article considers the gap between the roles of women as signs of modernization and agents of artistic creation in the late Ottoman Empire and the early Turkish Republic, between the 1880s and the 1950s. It investigates why, during an era of remarkable achievements in women’s education and participation in the public sphere, women trained as artists rarely succeeded in forging professional careers. It suggests that although useful as a mode of memorial, the retroactive enumeration of female artists from this period repeats the use of women as tropes of modernization rather than critically evaluating their historical opportunities to participate fully as agents in the modern public sphere.